Live and non-live pregnancy outcomes among women with depression and anxiety: a population-based study. - Lu Ban; Laila J Tata; Joe West; Linda Fiaschi; Jack E Gibson (PLoS ONE, 2012)
Background Women taking antidepressant or anti-anxiety medications during early pregnancy have high risks of non-live pregnancy outcomes, although the contribution of the underlying illnesses to these risks remains unclear. We examined the impacts of antenatal depression and anxiety and of commonly prescribed treatments on the risks of non-live pregnancy outcomes. Methods We identified all pregnancies and their outcome (live birth, perinatal death, miscarriage or termination) among women aged 15-45 years between 1990 and 2009 from a large primary care database in the United Kingdom. Women were grouped according to whether they had no history of depression and anxiety, a diagnosis of such illness prior to pregnancy, illness during pregnancy and illness during pregnancy with use of medication (stratified by medication type). Multinomial logistic regression models were used to compare risks of non-live outcomes among these groups, adjusting for major socio-demographic and lifestyle characteristics. Results Among 512,574 pregnancies in 331,414 women, those with antenatal drug exposure showed the greatest increased risks for all non-live pregnancy outcomes, relative to those with no history of depression or anxiety, although women with prior (but not currently medicated) illness also showed modest increased risks. Compared with un-medicated antenatal morbidity, there was weak evidence of an excess risk in women taking tricyclic antidepressants, and stronger evidence for other medications. Conclusions Women with depression or anxiety have higher risks of miscarriage, perinatal death and decisions to terminate a pregnancy if prescribed psychotropic medication during early pregnancy than if not. Although underlying disease severity could also play a role, avoiding or reducing use of these drugs during early pregnancy may be advisable.